PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR SISWA KELAS V TEMA 2 SUB TEMA 1 - Hugo, Riswanda; Tamba, Robenhart (Jurnal Merah Putih Sekolah Dasar, 2023)
This research by the low student learning outcomes on theme 2 subtheme 1in class V. This study aims This study aims to determine the effect of the Group Investigation Learning Model on student learning at outcomes on theme 2 subtheme 1 class at SDN 105327 Pardamean. This research method is experimental with One Group Pretest-Posttest Design. The subjects used in the study were class V The data collection tool used in this study is a test of student learning outcomes in the form of multiple choice as many 20 questions. The data analysis technique used is normality test, homogenity test, hypothesis, namely t-test with the help of Microsoft Excel Program. The resluts showed that there was a comparison of the average value in the pretest which was 53,43 while the posttest data had an average of 87,18 Based on the results of hypothesis testing performed with a significant = 0,05. then the obtained t table of 1,725 So that the criteria for drawing conclusions are tcount Ëƒ ttable namely 18,05 > 2,04. So it can be concluded that Ha is accepted with the statement that there is an influence from the use of the Group Investigation Learning. Keywords: Group Investigation Model, Learning Outcomes